PENGARUH PENERAPAN MODEL PEMBELAJARAN CONNECTING ORGANIZING REFLECTING AND EXTENDING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XII MIPA SMA NEGERI 2 PAYAKUMBUH - Khalid, M. Ikbal (Jurnal Edukasi dan Penelitian Matematika, 2023)
This research aimed to evaluate the comparison between two instructional models, namely the Connecting, Organizing, Reflecting, and Extending (CORE) model and direct instruction, on the mathematical concept comprehension of 12th-grade students at SMA Negeri 2 Payakumbuh. The research method employed a quasi-experimental approach with two sample groups, one as the experimental group implementing the CORE model, and the other as the control group receiving direct instruction. The results of the study indicated that students who underwent the CORE model demonstrated a better understanding of mathematical concepts compared to those who received direct instruction. These findings are relevant for enhancing the quality of mathematics education at the high school level and illustrate that interactive learning approaches like CORE can improve understanding of mathematical concept, particularly when adapted to students' needs. Keywords — Understanding of mathematical concepts, CORE, Direct learning